Attitude of the Students in Paramedicine School of Babol University of Medical Sciences about Electronic Registration - Haydeh Alaoddolehei; Mohsen Pourghasem (Babol University of Medical Sciences, 2014)
BACKGROUND AND OBJECTIVE: Making registration electronically is a way to facilitate registration process. Due to the significant role of the students in working with electronic system for educational process, the level of their satisfaction is important to find strength and weakness points of the system. Therefore, this study focused on the attitude of the students in Paramedicine Schools regarding to work with the electronic system registration. METHODS: This cross-sectional study was performed on 390 undergraduate students of Paramedicine School of Babol University of Medical Sciences in Semester 2 of 2012. The level of satisfaction was assessed by a questionnaire consisting of two sections in the terms of demographic characteristics and their attitude toward electronic registration. Data were analyzed by SPSS 18. FINDINGS: Findings showed that out of 390 participants, 32.6% were male and 67.4% were female. Mean age of the subjects was 20.7±2.9. 81.5% of the students were fairly and totally satisfied with electronic registration. Their main problem was disarrangement between courses and educational planning. Furthermore they requested for system promotion, more facilities and putting the plan and time of the classes in the system. CONCLUSION: Results showed that the students were satisfied with electronic registration and asked for solving the problems and system promotion. Therefore, they requested for more attention of stakeholders to reduce their attendance to the school for registration